(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The mites from the genus Eotetranychus bave frequently been found on various host plants in Turkey in recent years and bave already become important pests of some plants like apple, Populus and Crataegus. Because of a high resemblance, it is difficult to distinguish the species. Upon the advice of Prof. Dr. G. Dosse, I tried to follow the information and the keys given by Reeves (1963). Contrary to his findings I found no specificity as to the host plants of the species. Eotetranychus mites collected from Crataegus, Acer, Platanus and Pirus could all live and reproduce normally on both apple and Crataegus in my laboratory. Only the mites collected from Populus did not propagate as easily as others on apple trees. Besides, the individuals from the same host, even from ·the same leaf bave shown a large variation in the form of peritreme as may be seen in the figures. To exclude the possibility that the collected material might represent a mixed population, three generations of offspring from several pairs of parents were separately reared. The same variation was observed in every generation. Thus, I do not think that neither the specificity of host nor the form of peritreme can be considered as useful taxonomic characteristics for the species of Eotetranychus. The biological characteristics may be of a higher value.